2020
DOI: 10.3389/fphar.2020.00696
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Punicalagin on Osteoporosis by Inhibiting Osteoclastogenesis and Inflammation via the NF-κB and MAPK Pathways

Abstract: Postmenopausal osteoporosis is a worldwide disease characterized by reduced bone mineral density and increased fracture risk. Inflammatory bone loss due to excessive osteoclast bone resorption is significant in the pathogenesis and development of osteoporosis. Punicalagin (PUN) is a pomegranate fruit derivative and has potential antiinflammatory effects. However, the effect of PUN on osteoporotic bone loss has yet to be clarified. In this study, we investigated the effect of PUN on RANKL-induced osteoclast for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Targeting the ERK MAPK signaling pathway has been employed as a therapeutic strategy to treat cancer and neurological diseases, highlighting its importance in the regulation of these diseases [ 76 , 77 ]. Similarly, although there has yet to be an available therapeutic strategy that is designed to specifically target the ERK MAPK signaling pathway to treat osteoporosis, various other strategies such as estrogen, rhein-derived thioamide (RT), prostaglandin E2 (PGE2), and Src inhibitors, to name a few, have mechanisms involved in the regulation of the ERK MAPK signaling pathway [ 74 , 78 , 79 , 80 , 81 , 82 ]. Estrogen and PGE2 activate ERK to promote osteoblast differentiation, but estrogen also activates ERK to inhibit osteoclast differentiation, as mentioned above [ 74 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the ERK MAPK signaling pathway has been employed as a therapeutic strategy to treat cancer and neurological diseases, highlighting its importance in the regulation of these diseases [ 76 , 77 ]. Similarly, although there has yet to be an available therapeutic strategy that is designed to specifically target the ERK MAPK signaling pathway to treat osteoporosis, various other strategies such as estrogen, rhein-derived thioamide (RT), prostaglandin E2 (PGE2), and Src inhibitors, to name a few, have mechanisms involved in the regulation of the ERK MAPK signaling pathway [ 74 , 78 , 79 , 80 , 81 , 82 ]. Estrogen and PGE2 activate ERK to promote osteoblast differentiation, but estrogen also activates ERK to inhibit osteoclast differentiation, as mentioned above [ 74 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…Punicalagin (PUN) is a polyphenol isolated from pomegranate and displays a variety of pharmacological activities, of which antioxidant and anti-inflammatory are the most important [125,126]. It seems that antioxidant activity of PUN is mediated via its impact on Nrf2 signaling pathway.…”
Section: Natural Compounds In Ameliorating Doxorubicin-mediated Toxicitymentioning
confidence: 99%
“…Previously, it was reported that punicalagin would be beneficial in some diseases, including Alzheimer's disease [ 27 ], memory impairment [ 28 ], and endometritis [ 29 ], which is due to its inhibitory effects on MAPK and NF- κ B activation. Punicalagin treatment effectively inhibits proinflammatory cytokine, nuclear factor κ B (NF- κ B), and mitogen-activated protein kinase (MAPK) expression in vitro in osteoporosis [ 30 ]. Punicalagin which has potent anti-inflammatory effects could be beneficial for ankylosing spondylitis like chronic progressive inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%